Quantum chemical modeling of the inhibition mechanism of monoamine oxidase by oxazolidinone and analogous heterocyclic compounds - ERDEM, SAFİYE (TAYLOR & FRANCIS LTD, 2014)
Monoamine oxidase (MAO, EC 1.4.3.4) is responsible from the oxidation of a variety of amine neurotransmitters. MAO inhibitors are used for the treatment of depression or Parkinson's disease. They also inhibit the catabolism of dietary amines. According to one hypothesis, inactivation results from the formation of a covalent adduct to a cysteine residue in the enzyme. If the adduct is stable enough, the enzyme is inhibited for a long time. After a while, enzyme can turn to its active form as a result of adduct breakdown by beta-elimination. In this study, the proposed inactivation mechanism was modeled and tested by quantum chemical calculations. Eight heterocyclic methylthioamine derivatives were selected to represent the proposed covalent adducts. Activation energies related to their beta-elimination reactions were calculated using ab initio and density functional theory methods. Calculated activation energies were in good agreement with the relative stabilities of the hypothetical adducts predicted in the literature by enzyme inactivation measurements.
Keywords: Adduct dissociation; adduct stability; dihydrofuranone; enzyme inhibition; oxazolidinone; pyrrolidinone; ACTIVE-SITE; AMINE-OXIDATION; B INACTIVATORS; AROMATIC CAGE; DRUG TARGET; 1-PHENYLCYCLOPROPYLAMINE; BENZYLAMINE